(3JWhQ UhQ h eQGMd GdJbGVj aj GdeLJeYGJ GdHTQjI GdbOjeI (B/s - (3gTGe jhSa agej jhSas; (3Wg YhV ZGRi (B: s; (3eMehO YR GdYQH GdSbGs; (3fRjg eMeO UGOb GdegOjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3JfGhdJ GdOQGSI JWhQ UhQ h eQGMd GdJbGVi ai GdeLJeYGJ GdHTQjI GdbOjeI(B: (3MjK Gf dUhQ GdJbGVi OhQ cHjQ ai JWhQ GdacQ GdbGfhfi YGeI h GdacQ GdbVGFi NGUI(B: (3h GdJCcjO Ydi GdOhQ GdcHjQ (B- (3ddbVGA(B- (3ai GdJhajb Hjf GdhGbY h GdbGfhf(B: (3h GdMaGX Ydi JQGHW GdfXGe GdbGfhfi h JeGScg(B: (3aGdbVGA OhQg OhQ GHOGYi JWhQi(B....(3h bO JYQVJ GdOQGSI deaghe GdbVGA(B: (3h GdJejR Hjfg h Hjf GdhdGjGJ GdCNQi (B((3hdGjI GdJMcje(B: (3hdGjI GdMSHI(B: (3hdGjI GdeXGde(B: (3hdGjI GdaJhi(B): (3h cPdc JfGhdJ GdOQGSI eGgjJg h eagheg YfO GdGaQGO h YfO GdeLJeYGJ GdHTQjI GdbOjeI(B: (3h HjfJ GUhd eHOC GdYOd GSGS GdMce (B. (3hJfGhd UhQ GdJbGVi ai GdeLJeYGJ GdHTQjI GdbOjeI(B: (3gi GdJUGdM h UhQg h GdJMcje h CfhGYg h eQGMd JWhQ GdbVGA(B. (3h JYQV ddbhGYO GdJi JMce UhQ GdJbGVi aj GdeLJeYGJ GdHTQjI GdbOjeI(B: (3eKd bhGYO GdOjf h JbGdjO GdYQa h GdTQGFY GdhVYjI(B. (3h QcR Ydi fJGFL JWhQ UhQ h eQGMd GdJbGVi dOi GdeLJeYGJ GdHTQjI GdbOjeI(B: (3MjK CUHM GdbVGA gh bVGA GdOhdI(B: (3GdbVGA GdefXe(B: (3GdbVGA GdPj JJhdi GdOhdI GNJjGQ GaQGOg h JfajP GMcGeg h Sf fXeg h bhGYOg(B. (3aj GdOhdI GdaQYhfjI h GdOhdI GdjhfGfjI h GdOhdI GdQheGfjI(B: (3h GdOhdI GdESdGejI(B.... (3h HjfJ GdOQGSI aj GdNGJeI Gge GdfJGFL GdJi GfJgJ GdjgG h GdJj JJab eY eG GSJgOaJg GdOQGSI s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg (B2015.s
(3HHdjhLQGajG(B: (3UaMGJ (B435-453.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdfXe GdbGfhfjIs; (3GdJMcjes; (3GdbVGAs; (3GdJMcjes -- (3JGQjNs -- (3eUQ s; (3eUQs -- (3bhGfjf hJTQjYGJs -- (3JGQjNs; (3GdjhfGfs -- (3bhGfjf hJTQjYGJs -- (3JGQjNs; (3GdJbGVis; (3GdeLJeYGJ GdHTQjI GdbOjeIs; (3JWhQ GdacQ GdbGfhfis; (3eUQ GdaQYhfjIs; (3GdJbGVj aj GdOhdI GdESdGejI s; (3GdJbGVj GdOhdI GdQheGfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhfs